Music in E. L. Doctorow’s novel “Ragtime”. - Hladkoskok, Lesia; Muradkhanian, Iryna; Semen, Halyna (Видавничий дім «Гельветика», 2022)
The article is devoted to the theme of music in the novel by E. L. Doctorow «Ragtime». The novel was published in 1975, became a bestseller and got a screen version. The writer turned to the events of the beginning of the XX-th century not by chance, as at that time in the USA people greatly admired rag not only as a kind of jazz, but as a style, a way of living. The novel immediately arose discussions, was translated into many languages and got numerous reviews both positive and negative. Literary criticism, theory of literature defined the role of the writer, his peculiar outlook. The connection of the novel with the music of ragtime had been analyzed from the point of view of literature study, whereas the linguistic aspect needed further investigation and that became the aim of the given article. A key word ragtime, its origin and usage, the functions in the sentence help understand the peculiarities of the novel. One of the protagonists Coalhouse Walker Junior is a professional pianist. His fate and his beloved Sarah’s fate are tragic, he stands up to defend his honor, but perishes in unequal battle. The writer combines real figures, documentary materials with imagined, artistically reinterpreted ones. Music terminology, words belonging to lexico-semantic group «Music» describe America of that time, they occur in the contexts where author with their help uses stylistic devices: epithets, metaphors, similes. Music becomes the background of the depicted events, influences the development of the plot, shows the characters and describes the appearance of the leading and supporting protagonists of the literary work, makes the narrative true-to-life, enlivens old times. The novel is characteristic of peculiar syntax that corresponds the rhythm of ragtime. This is created by the reiteration of extended and unextended sentences, anaphoric repetition of personal pronouns, enumeration, sometimes very extended. In the novel phraseological units connected with music were not fixed. Music in the novel is opposed to other sounds that are far from being melodious, but are sharp and bothering. The destinies of protagonists are intertwined and the ragtime itself disappears as does the sound of music. Perspectives of investigation may be the comparison of the novel with other literary works of the novelist who in his literary activity was constantly looking for new ways, experimented with the material and never repeated what he had already achieved.
Keywords: ragtime; music terms; stylistic devices; syntax; novel